Amplicon of 16s Rrna Gene Sequencing of Fertilized Volcanic Soils from Southern Chile - Tello-Reyes, M; Valdes-Parra, N (American Society for Microbiology, 2021)
The volcanic soils of Chiloé Island, Chile, have physical and chemical characteristics that affect their productivity. We report here a 16S rRNA gene analysis that characterizes the predominant microbial communities in volcanic soils of Chiloé either in the presence or absence of fertilization. The major phyla identified were Proteobacteria, Acidobacteria, and Actinobacteria. © 2021 American Society for Microbiology. All rights reserved.